IMPLEMENTASI MANAJEMEN STRATEJIK DAN PENGARUHNYA TERHADAP KEPEMIMPINAN STRATEJIK DAN KINERJA ORGANISASI STUDI PADA DINAS KEBUDAYAAN PROVINSI RIAU - Leismana, Taufik Indra; Machasin, Machasin; Jahrizal, Jahrizal (Jurnal Tepak Manajemen Bisnis, 2018)
Strategic Management Implementation and Its Influence on StrategicLeadership and Organizational Performance at Culture Department of RiauProvince, under the guidance of Machasin and Jahrizal.This study aims to see the effect of strategic planning, strategicimplementation, evaluation and control of strategic management onorganizational performance mediated by Strategic Leadership.This research uses quantitative method. Location of research in PekanbaruKebuayaan Agency. Determination of the sample using census method with allmembers of the population as subject studied were as many as 74 respondents.Methods of data collection in this study include questionnaires, interviews, andobservation. Data analysis method used Path Analisys using Partial Least Squere(PLS).The results of this study obtained feasible results and can be used as the basisfor making policy for Culture Department of Riau Province. This study concludesthat strategic management implementation has significant influence on strategicleadership, strategic management implementation has significant effect onorganizational performance, then strategic leadership has significant effect onorganizational performance. It is recommended to improve the performance of itsorganization especially that leads to change or innovation, improvingmanagement functions so as to improve organizational performance and enhanceits strategic leadership through capability so as to gain strong strategicleadership and real impact to improve the performance of Riau Province CultureAgencys organization